Identification of resistance sources to cereal cyst nematode, Heterodera avenae Wollenweber in barley (Hordeum vulgare L.) - koulagi, Ramanna; Kaur, Simarjit; Bishnoi, satyapal P.; Kanwar, Rambir Singh (Journal of Cereal Research, 2018)
A field study was carried out to identify the sources of resistance for cereal cyst nematode in Barley at three locations; Ludhiana, Durgapura and Hisar during three crop seasons from 2015-18. Out of 625 screened entries at three locations, none of the entry was found to be resistant to all the three populations, however, the four lines i.e. RD-2977, BH-959, RD-2794 and RD-2957 were found resistant to Jaipur and Hisar CCN population only. Further, PL-874 (2015-16), RD-2927 (2016-17) and BH-946 (2017-18) were found moderately resistant to Ludhiana and Jaipur populations. These results clearly indicate that the Ludhiana population was more virulent than the other two populations. Therefore, plant breeders can use PL-874, RD-2927 and BH-946 to breed barley varieties resistant against Ludhiana CCN populations.Â Doi.org/10.25174/2249-4065/2018/83680